Association of psychological stress with risk of dementia: A systematic review and meta‐analysis. (31st December 2021) - Franks, Katherine H; Bransby, Lisa; Saling, Michael M; Pase, Matthew P
Abstract: Background: With no effective disease‐modifying treatments, there is a need to identify lifestyle risk factors that may prevent or delay the onset of dementia. One proposed risk factor is psychological stress. Although many studies have investigated the association between stress and dementia, to our knowledge, no meta‐analysis has examined this. The current study investigated the association between different aspects of psychological stress (including neuroticism, stressful life events and perceived stress) and the risk of incident dementia in adults without cognitive impairment. Method: The study was prospectively registered and conducted in accordance with PRISMA guidelines. PsycINFO, Embase and MEDLINE were searched for eligible observational, prospective studies from database inception to October 2020. Pooled hazard ratios (HRs) were generated using random‐effects models to separately examine each aspect of stress in relation to the incidence of all‐cause dementia and Alzheimer's disease (AD) dementia. Result: Of the 1607 studies screened, 15 (18 cohorts) were included in meta‐analyses. Across studies, higher perceived stress was significantly associated with an increased risk of all‐cause dementia (Cases/Total N = 203/1, 882: hazard ratio [HR] = 1.44, 95% confidence interval [CI] = 1.07‐1.95). Exposure to two or more stressful life events (versus none) was also significantly associated with an increased risk of all‐cause dementia (Cases/Total N = 3, 352/11, 597: HR = 1.72, 95% CI = 1.14‐2.60), while one or more stressful life events was not. Higher neuroticism was significantly associated with an increased risk of AD dementia (Cases/Total N = 497/4, 771: HR = 1.07, 95% CI = 1.01‐1.12), but not all‐cause dementia. Conclusion: Psychological stress in adulthood is associated with an increased risk of dementia. Further research is needed to clarify the mechanisms underlying these associations.